PERAN MODAL INTELEKTUAL TERHADAP KINERJA DOSEN DENGAN KOMITMEN SEBAGAI VARIABEL MODERATING (MOTIVASI, 2023)
Purpose– This study aims to explore and prove whether there is an influence of Human Capital, Spiritual Capital and Commitment on PTS performance. Design/methodology– Data collection uses research instruments, namely questionnaires and documentation. data analysis is mixed methods with the aim of testing the hypotheses that have been set then the numbers are described. The setting for this research was PTS lecturers at Region II Higher Education Service Institutions, namely Palembang City. The number of samples is based on Ferdinand's approach (2006) that the sample size is determined by 25 times the number of independent variables, namely 25 x 4 = 100 samples from 7 PTS. The sampling technique is Snowball sampling. The measurement scale uses a Likert scale. Data analysis techniques using SEM PLS. Findings - The results show that commitment and spiritual capital have a positive value and have a significant effect on lecturer performance. For human capital does not affect lecturer performance, then organizational commitment cannot moderate the relationship between human capital and spiritual capital with lecturer performance.